Influences of the operating variables of acetosolv pulping on pulp properties of oil palm frond fibres - Wanrosli, W.D.; Mazlan, I.; Law, K.N.; Nasrullah, R. (Maderas. Ciencia y Tecnología, 2025)
The effect of acetosolv pulping variables viz. pulping time, temperature, catalyst (HCl) and acetic acid on oil palm frond fibres was investigated. The following conditions were found to be optimum to pulp frond fibres: 140 ºC, 0.5% HCl, 75% acetic acid, and 1/10 solid/liquor ratio. Under these conditions we could obtain these properties: Kappa number 13-16, zero-span tensile breaking length – 83 km, sheet density – 0.57 g cm-3, tensile index – 48 N m g-1, tear index – 5.4 mN m2 g-1, brightness – 16% ISO and opacity – 98%. Higher values of these operating parameters would degrade the fibre characteristics such as zero-span tensile breaking length, tensile index, and sheet density.